Variabilidade genética de milho (Zea mays), feijão (Phaseolus vulgaris) e cucurbitáceas em unidades de produção agroecológica na região sul do Rio Grande do Sul - Rodrigues, Walter Fagundes (2012)
The objective of this study was to demonstrate the agrobiodiversity of cucurbits, maize (Zea mays) and beans (Phaseolus vulgaris), and methods of management and farming practices used, both for their production and conservation of genetic resources, based on farmers ecological basis of the southern Rio Grande do Sul visits were carried out on 11 family farms, and through interviews, 37 landraces were collected which were duly cataloged and stored in Active Germplasm Bank of Embrapa Clima Temperado.